Science teachers’ perspectives on the integration of the quran in science learning - Fawarni Hj Ahmad; Zanaton H. Iksan (Penerbit Universiti Kebangsaan Malaysia, 2023)
The integration of the knowledge in Quran and Science is significant and timely. The truth of Quran contents is proven by the phenomenon of Science. However, Science education in Malaysia which is too similar to Western learning style, focuses more on student achievement in examinations. Therefore, efforts to integrate Science and the Quran do not occur in formal teaching and learning activities in the classroom. Thus, this article discusses secondary school science teachers’ perspectives on the Quran-integrated Science learning approach. This study uses qualitative design methodology by conducting interviews with four Science teachers at Sekolah Menengah Kebangsaan Agama (Tahfiz Model Ulul Albab) in Negeri Sembilan. Data analysis was performed using Atlas.ti software version 9. Thematic analysis method is used to analyze the data based on a fixed comparison of each study findings. The results of the interviews showed that apart from the Islamic vision of Science teachers who are excited to implement Al-Quran Integrated Science learning, there are 4 main factors that need to be examined namely (i) existing problems in the educational environment, (ii) lack of adequate knowledge and skills , (iii) suggestions on the need for tools to implement the integration of science with the Qur’an and (iv) the expectations of Science teachers on the integration of this revelation knowledge in the teaching of Science subjects. This study is expected to be a source of information to the drafters of the Science and revelation knowledge integrated curriculum which is believed to be able to produce generation of ulul albab students who are balanced in academic and spiritual aspects, especially for use in religious schools and Tahfiz Science.